Losing reproduction: effect of high temperature on female biochemical composition and egg quality in a freshwater crustacean with direct development, the red cherry shrimp, Neocaridina davidi (Decapoda, Atyidae) - Baliña, Sofía (2018)
Maternal provisioning is particularly important in invertebrates with abbreviated development because large energy reserves must be provided for the developing embryo. In this context, the objective of the present study was to analyze in an aquatic invertebrate with direct development the effect of temperature on female biochemical composition and reserve allocation to maturing ovaries, which determine egg quality. A decapod crustacean, the freshwater shrimp Neocaridina davidi, was used as experimental model. Newly hatched juveniles were exposed to 28 °C or 33°C. Females showed mature ovaries and spawned at 28 °C (control ovigerous females), but no ovigerous female was found at 33 °C. After a 200-day period, half of the females at 33 °C were transferred to 28 °C, where they rapidly showed mature ovaries and spawned (trans-ferred ovigerous females). Ovigerous females and females that did not spawn at 28 °C (control non-ovigerous females) and at 33 °C (high-temperature non-ovigerous females) were sacrificed to determine their biochemical composition. The number, volume, weight, and biochemical composition of the eggs from transferred and control ovigerous females were also analyzed as indicators of their quality. Female biochemical composition was not influenced by temperature, because control and high-temperature non-ovigerous females had similar lipid, protein, and glycogen contents. However, ovarian maturation and spawning were inhibited at 33 °C, which indicates a negative effect of this temperature on nutrient transfer to the oo-cytes. This effect was rapidly reversed after females were moved to 28 °C; the eggs from control and transferred ovigerous females were of similar quality, except for a lower protein content in the latter. The present results provide valuable information on reserve allocation to reproduction under thermal stress.